2009
DOI: 10.1007/s10447-009-9078-0
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Ego Development and Multicultural Competence During Internship

Abstract: This research involved an exploratory intervention to determine the effectiveness of using a deliberate psychological education (DPE) approach that incorporated issues of ethics, multicultural competence, oppression and diversity. The study attempted to discern if the DPE model used could make a difference in the promotion of ego development (which subsumes moral development) and multicultural knowledge and awareness of counselor interns. The intervention group showed significant gains compared to comparison g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…and that students should be given periodic feedback concerning their performance during their counselor education program (Standard F.9.a.). Students need time to process these conflicts in a safe environment while receiving guidance and support (Brendel, Kolbert, & Foster, ; Cannon & Frank, ; Minnix, ; Schmidt, McAdams, & Foster, ).…”
Section: Recommendations For Counselor Educatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…and that students should be given periodic feedback concerning their performance during their counselor education program (Standard F.9.a.). Students need time to process these conflicts in a safe environment while receiving guidance and support (Brendel, Kolbert, & Foster, ; Cannon & Frank, ; Minnix, ; Schmidt, McAdams, & Foster, ).…”
Section: Recommendations For Counselor Educatorsmentioning
confidence: 99%
“…Cannon and Frank () found that a deliberate psychological education (DPE; Mosher & Sprinthall, ) embedded in the internship class promoted cognitive complexity and multicultural competence. An effective DPE incorporates five conditions: (a) a new role‐taking experience (that of a counselor‐in‐training), (b) careful guided reflection, (c) a balance between the new experience and reflection, (d) continuity (ideally 6–12 months), and (e) an environment that balances support and challenge.…”
Section: A Structured Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, multicultural personal growth groups may promote ethnic identity development and social‐cognitive maturity in graduate counseling students (e.g., Rowell & Benshoff, 2008; Villalba & Redmond, 2008). Higher levels of ethnic identity development are supportive of multicultural counseling competence in counselors (e.g., Evans & Foster, 2000; Middleton et al, 2005; Vinson & Neimeyer, 2000), and increased levels of social‐cognitive development foster cognitive complexity, a significant counseling disposition (Cannon & Frank, 2009). However, research is needed to determine the effectiveness of multicultural pedagogical strategies in counselor education (e.g., Hill, 2003).…”
mentioning
confidence: 99%